Penerapan Nilai Nilai Bela Negara Dalam Menghadapi Tantangan Era Digital - Erva Yunita; Ika Yanuar Margiyanti; Suryani Alawiyah; Irwan Triadi (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
The meaning of defending the country is a manifestation of our love for the Unitary State of the Republic of Indonesia. Defending the State is not the responsibility of the TNI or Police alone, but defending the State is our collective responsibility as citizens of the Indonesian community to protect Indonesia from all kinds of threats both from within and outside in order to maintain the integrity of the Unitary State of the Republic of Indonesia. Along with the development of technology, Indonesia is currently entering the era of digitalization. In the era of digitalization, attacks or threats to the country are not only in the form of physical attacks, but also cyber attacks that attack a country in the economic, political and military fields using attacks due to technological advances. This is the focus of this research. The question of this research is what are the factors that influence the challenges of the digital era in society and how to apply the value of defending the country in facing the challenges of the digital era. To obtain answers, this research uses yuridis normative methods or library research, meaning that this research is based on on library sources to discuss the problems that have been formulated. From the results of this research, it can be concluded that in realizing actions to defend the country, it is necessary to instill a sense of love for Indonesia's air, and by remembering that Indonesia is a country with a lot of diversity, it is necessary to instill a sense of tolerance in the minds of the souls of Indonesian citizens. One of the very important basic elements of the digital era is being critical in responding to content. Indonesian citizens today must be smarter in absorbing content and information and encourage Indonesian citizens and society to always be critical and suspicious, especially regarding content that is too bombarded, meaningless, and full of nuances of hatred To ensure that the unitary Republic of Indonesia remains intact and peaceful.